The Influence Brand Image and Halal Awareness on Laneige Korean Cosmetic Purchasing Decisions: Using the Theory of Planned Behavior Model - Komariah, Siti Hajar; Prabawa, Bijaksana; Putri, Mediany Kriseka; Praptono, Budi (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
The cosmetics industry in Indonesia is currently experiencing rapid growth, characterized by the increasing presence of both local and international brands, such as Laneige, which continues to gain popularity among consumers. This study aims to examine the relationship between brand image and Halal awareness in shaping consumer purchase intentions and decisions. A quantitative research approach with the proposed model being tested and validated through structural equation modeling based on data from 250 respondents. The findings indicate that both brand image and Halal certification have a significant influence on Indonesian consumers' adoption of cosmetic products. In light of these results, it is recommended that cosmetic business managers and brand owners promptly obtain Halal certification to alleviate any consumer confusion regarding product usage.